A Retrospective Study of Efficacy and Toxicities of Rituximab in Combination with Chemotherapy for NHL patients in Bangladesh (Anwer Khan Modern Medical College Journal, 2015)
Bacground: In Bangladesh conventionally CHOP therapy is widely practiced for the treatment of NHL patient. But refractory/ relapse case is highly observed in CHOP therapy. Reports of different clinical trials showed that addition of Rituximab with CHOP therapy dramatically increase the progression free survival (PFS) and overall survival (OS) of patients.Methodology: To analyze the response and toxicities of NHL patients treated with Rituximab in combination with other chemotherapy regimen admitted in Anwer Khan Modern Hospital, City Hospital and United Hospital in Dhaka, Bangladesh. Response and toxicities of patients admitted to three institutions between May 2003 to December 2006 were analyzed. A total of 30 patients were observed in this study. Patients received up to 6-8 cycles of Rituximab in combination with CHOP for every 3 weeks as an induction therapy. Maintenance therapy was given to 6 patients at 3 months interval for up to 2 years.Result: After a median follow up period of 6 years patients were evaluated on the basis of response criteria. Out of the 30 patients 3 patients did not completed 6 cycle R-CHOP treatment regimen. 13% of the patients were refractory and died before completing therapy. With R-CHOP combination 47% of the patients experienced complete response. Partial response was observed in 20% of the patients. In this study 6% of the patients did not get response from the therapy. Haematological toxicity included grade 3-4 neutropenia 13%, anaemic 4%, febrile neutropenia 17% and thrombocytopenia 11%. Non-haematological toxicity included grade 2-3 nausea or vomiting 18%, grade 3 fatigue 12%.Conclusion: Addition of Rituximab as an immunotherapy option with chemotherapy regimen provides excellent response to Bangladeshi patients diagnosed for Diffused Large B Cell Lymphoma (DLBCL). Further study needs to be done to evaluate efficacy and toxicity profiles of patients treated with other chemotherapy regimen who were not eligible for CHOP regimen.Anwer Khan Modern Medical College Journal Vol. 6, No. 1: January 2015, Pages 28-34